The Effects of Research & Development Funding on Scientific Productivity: Academic Chemistry, 1990-2009 - Rosenbloom, Joshua L.; Ginther, Donna K.; Juhl, Ted; Heppert, Joseph A. (PLOS ONE, 2015)
This article examines the relationship between Research & Development (R&D) funding and the production of knowledge by academic chemists. Using articles published, either raw counts or adjusted for quality, we find a strong, positive causal effect of funding on knowledge production. This effect is similar across subsets of universities, suggesting a relatively efficient allocation of R&D funds. Finally, we document a rapid acceleration in the rate at which chemical knowledge was produced in the late 1990s and early 2000s relative to the financial and human resources devoted to its production.